INDONESIA-JAPAN ECONOMIC PARTNERSHIP AGREEMENT IMPACT FOR INDONESIA AND JAPAN - Sigit Setiawan (Jurnal Ilmiah Ekonomi Bisnis, 2012)
The study is an impact assessment of Indonesia-Japan Economic Partnership Agreement(IJEPA) trade agreement in goods for Indonesia and Japan countries. The econometricanalysis approach has been used to assess the impact of IJEPA toward the two countriesfrom two sides : export contribution to national income and the export contributiongrowth. The result is at macro level, in which both Indonesia and Japan gain benefits ofIJEPA. Yet, Indonesia received more benefits than Japan from the increased exportcontribution to national income by amount and by percentage, and from leverage towardthe export contribution.Key Word : free trade area, preferensia tradel, export, impact assessment